Strategi Pengembangan Karakter Toleransi Santri Putri Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan - Ani Renita; Ratika Novianti; Halimatus Sa’diyah (Departement of Mathematics Education, 2024)
This research is motivated by: Most of the students already understand about tolerance, but there are still many students who do not know the character of tolerance and many students who already know how to respect but there are still many students who do not understand the attitude of mutual respect between students because they still often prioritize themselves. This study aims to analyze: (1) the strategy for developing the character of tolerance of female students of the Hidayatul Mubtadiin Islamic Boarding School?. (2) The impact of developing tolerance values ​​on students at the Hidayatul Mubtadiin Islamic Boarding School?. After the data is collected, the data will be tested for validity using the data triangulation technique, in this case the author uses the source triangulation technique, after that the data analysis technique will be carried out using 3 stages, namely, data reduction, data presentation, and drawing conclusions. This research is a Qualitative Research, the type of research is descriptive qualitative with research subjects of 3 Ustadzah and 3 female students of the Iqro' class at the Hidayatul Mubtadiin Jati Agung Islamic Boarding School. Data collection techniques in this study were through observation, interviews, and documentation. The results of this study indicate that: the strategy for developing the tolerance character of female students at the Hidayatul Mubtadiin Islamic Boarding School is implemented with the following system: Habituation The development of tolerance values ​​at the Hidayatul Mubtadiin Islamic Boarding School is implemented through direct practice with students in the daily life of the Islamic boarding school, namely queuing in the bathroom when taking ablution, bathing, washing, and defecating, queuing when taking food, and in order to form an attitude of tolerance between students, the management will also punish students who take what is not their right or are often called ghosob. Learning is carried out during other learning activities such as during routine sermons on Sunday nights and religious lectures after each Dhuhur and Asr prayers.